2010
DOI: 10.1029/2010jd014140
|View full text |Cite
|
Sign up to set email alerts
|

Wave‐induced transport of atmospheric constituents and its effect on the mesospheric Na layer

Abstract: [1] Extensive observations of winds, temperatures, and Na densities between 80 and 105 km at the Starfire Optical Range, New Mexico, are used to characterize the seasonal variations of the vertical flux of atomic Na and its impact on the Na layer. The largely downward Na flux and its convergence enhance the transport of Na from meteoric sources above 90 km to chemical sinks below 85 km, altering the height, width, and abundance of the Na layer. From theoretical considerations, it is shown that the effective ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 60 publications
(132 citation statements)
references
References 25 publications
7
125
0
Order By: Relevance
“…In fact, previous observations have shown that the associated correlation coefficients among temperature, Fe and Na densities are often quite high (absolute values greater than 0.7) but the sign can vary rapidly near the peaks of the Na and Fe layers [Gardner and Liu, 2010;Gardner et al, 2005;Chen and Yi, 2011]. For chemically active constituents such as Fe and Na, the fluctuations arise from purely dynamical effects associated with wave-induced displacement, as well as chemical effects associated with the perturbed production and loss reactions involving the species.…”
Section: Lidar Observationsmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, previous observations have shown that the associated correlation coefficients among temperature, Fe and Na densities are often quite high (absolute values greater than 0.7) but the sign can vary rapidly near the peaks of the Na and Fe layers [Gardner and Liu, 2010;Gardner et al, 2005;Chen and Yi, 2011]. For chemically active constituents such as Fe and Na, the fluctuations arise from purely dynamical effects associated with wave-induced displacement, as well as chemical effects associated with the perturbed production and loss reactions involving the species.…”
Section: Lidar Observationsmentioning
confidence: 99%
“…However, because the Fe and Na density fluctuations are dominated by dynamics, it is possible to derive useful analytical models for the Fe and Na fluctuations and their covariance functions using the approach developed by Gardner and Liu [2010] for a spectrum of wind perturbations. The key derivations are summarized in Appendix A.…”
Section: Theoretical Studies and Comparison To Observationsmentioning
confidence: 99%
See 3 more Smart Citations